Caged capsaicins: new tools for the examination of TRPV1 channels in somatosensory neurons - Gilbert, Daniel; Lehmeyer-Funk, Katharina; Möhrlen, Frank; Frings, Stephan (ChemBioChem, 2007)
The vanilloid capsaicin, N-(4-hydroxy-3-methoxybenzyl)-8-methylnon-6-enamide, is the pungent ingredient of chili peppers and is used in pain research as an activating ligand of heat-sensitive transduction channels in nociceptive neurons. Here we describe the synthesis and application of two capsaicin derivatives modified at the hydroxy function of the vanillyl motif: α-carboxy-4,5-dimethoxy-2-nitrobenzyl-caged (CDMNB-caged) capsaicin and {7-[bis(carboxymethyl)amino]coumarin-4-yl}methoxycarbonyl-caged (BCMACMOC-caged) capsaicin. These compounds show dramatically reduced pungency, but release active capsaicin upon irradiation with UV light. CDMNB-caged capsaicin can be used to perform concentration-jump experiments, while BCMACMOC-caged capsaicin is membrane-impermeant and can be applied selectively to the intracellular or extracellular sides of a plasma membrane. Both compounds can serve as valuable research tools in pain physiology.